1986
DOI: 10.1159/000167173
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Focal Segmental Glomerulosclerosis

Abstract: We describe the early lesion of focal segmental glomerulosclerosis (FSGS) as it appeared in 2 cases of recurrent FSGS with early transplant nephrectomies (approximately 2 months) due to uncontrollable nephrotic syndrome. A quantitative evaluation showed that these lesions were present more often in the glomeruli of the juxtame-dullary cortex. Epithelial cell proliferation and detachment and foam cells were seen frequently and were considered the hallmarks of the early lesion of FSGS. Hyaline deposits are secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Second, we performed a separate analysis of cortical versus juxtamedullary nephrons, stimulated by the observation that the latter are more severely injured in many disorders including AN 22 , 23 , 24 and are more frequently and more severely affected by glomerulosclerosis. 25 , 26 Our data suggest that juxtamedullary nephrons, which represent only 20% of glomeruli, harbor more podocytes because they are larger, 27 , 28 , 29 face substantially more ADR-induced podocyte loss, and recover less from injury because they are endowed with less Pax2+ progenitors per podocyte. In contrast, cortical nephrons are smaller but much more numerous, 27 , 28 have less podocytes, and lose only few podocytes during AN, which they can recover more easily because cortical nephrons have more Pax2+ progenitors per podocyte.…”
Section: Discussionmentioning
confidence: 70%
“…Second, we performed a separate analysis of cortical versus juxtamedullary nephrons, stimulated by the observation that the latter are more severely injured in many disorders including AN 22 , 23 , 24 and are more frequently and more severely affected by glomerulosclerosis. 25 , 26 Our data suggest that juxtamedullary nephrons, which represent only 20% of glomeruli, harbor more podocytes because they are larger, 27 , 28 , 29 face substantially more ADR-induced podocyte loss, and recover less from injury because they are endowed with less Pax2+ progenitors per podocyte. In contrast, cortical nephrons are smaller but much more numerous, 27 , 28 have less podocytes, and lose only few podocytes during AN, which they can recover more easily because cortical nephrons have more Pax2+ progenitors per podocyte.…”
Section: Discussionmentioning
confidence: 70%
“…2,3 These studies, confirmed in human FSGS that recurs post kidney transplant 4 , have shown that podocyte injury exemplified by cell body attenuation, foot process effacement, pseudocyst formation and microvillous transformation, is the earliest feature of FSGS. In human FSGS, these electron microscopic findings may be seen weeks to months prior to the development of visible lesions by light microscopy.…”
Section: Morphological Studies Place Podocytes At the Center Of Fsgsmentioning
confidence: 89%
“…4 Plasmapheresis has been successfully used to treat a number of transplant recipients with early recurrence of FSGS. 5 Interestingly, successful retransplantation of a kidney allograft from a patient with recurrent primary FSGS who did not respond to therapy to a patient whose primary kidney disease was not FSGS, has been reported.…”
Section: Clinical Settingmentioning
confidence: 99%